Review of Islamic Law Against Negative Campaigns in Regional Head Elections - Yondrizal (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Negative campaigns in regional head elections have become a phenomenon that often appears, not only in Indonesia, but also in various other countries. In the perspective of Islamic law, this negative campaign practice can be linked to the principles of morality and ethics. This is mainly related to the prohibition on spreading slander (namimah), swearing (ghibah) and damaging individual honor. The results of the study show that negative campaigns in regional head elections that contain elements of slander, lies or insults clearly conflict with the values of justice, truth and morals that are upheld in Islam. On the other hand, criticism that is constructive, fact-based, and aims for the benefit of the people, is seen as acceptable in Islamic law, as long as it continues to comply with Sharia norms. This study suggests the importance of strengthening Islamic political ethics education for the community and prospective regional heads, with the aim of building a healthier and more dignified democratic process in accordance with Islamic teachings.